The Influence of Work Environment, Work Discipline, and Work Stress on Employee Performance of the Directorate General of Regional Financial Development, Ministry of Home Affairs - Azahra, Diah; Erica, Denny; Rachmah, Siti Mabrur (MultiTech Publisher, 2024)
Human resource management is included in organizations that focus on human resources. Human resources or human One of a company's most crucial components is its resources, particularly at the Ministry of Home Affairs' Directorate General of Regional Financial Development. The analytical instrument employed was Spss29.0 ver.2023, in this study 40 respondents were used as the study population and the research sample technique used was saturated sampling technique, and questionnaires were used as a data collection tool. From validity test and reliability test. The reliability test results are considered reliable with the Cronbach alpha value r count 0.494 > r table 0.304, and the variables of work environment, work discipline, and work stress are considered valid because the value of r count > r table. The work environment variables of work discipline and work stress have an effect of 30.8% on employee performance, according to the results of the determination test for the R square value, which is 0.308 or 30.8%. The remaining variables are influenced by other variables that were not examined. According to the F test, Fcount (5,339) is greater than Ftable (1.92). Thus, the working environment, work discipline, and work stress all have an impact on employee performance at the same time.